Reassessing Nepotism: Wederrechtelijk and Onrechtmatige Daad in Indonesian Law - Murtadho, Nazhif Ali; Warjiyati, Sri (Faculty of Law, Universitas Lampung, 2024)
This research examines nepotism as a form of Corruption, Collusion, and Nepotism (KKN), which has significantly undermined social and institutional order in Indonesia. The problem stems from the negative impacts of KKN on community welfare, resource misuse, and the erosion of public integrity and morals. The main goal of the paper is to analyze nepotism from a positive legal perspective by exploring the conceptual differences between